CEU Graduation Ceremony 2002 - Part 5
Continuation of the recording of the CEU’s 11th Graduation Ceremony on June 20, 2002. It contains the recording of Yehuda Elkana reading a letter from Péter Medgyes (Under-secretary of State for International Relations from the Ministry of Culture and Education, Budapest), who could not attend the ceremony yet wished to salute and congratulate the graduates of the academic year 2001/2002. Moving of the tassels, the symbolic gesture of becoming Alumni is also recorded here. The ceremony ends with the academic recessional.